69 Carcinoma Prostate With Unusal Site & Unusual Mode of Metastasis - Ab Wahid Mir; Syed Nisar Ahmad; Syed Arshad Mustafa; Faisal Rashid Guru; Shah Naveed (Dr. Annil Mahajan, 2022)
Metastasis from prostate cancer to sigmoid colon without direct extension is rarest of rare finding. Patients of ca prostate presenting with lower gastro-intestinal symptoms needs complete evaluation to rule out metastasis to colorectal region from prostatic adenocarcinoma. As the primary management of primary colorectal carcinoma is surgery, whereas in case of metastatic lesion from ca prostate requires hormonal and /or chemotherapy. Therefore, distinction is essential to tailor proper treatment. As many as 20% of patients of ca prostate are diagnosed to have distant metastases at the time of presentation . We are reporting a patient of ca prostate who presented with metastatic polyps in sigmoid colon without any intra-abdominal disease.